Neotrombicula roubaudi - Stekolnikov, Alexandr A. (Zenodo, 2018)
Neotrombicula roubaudi (Vercammen-Grandjean, 1956) Trombicula (Neotrombicula) roubaudi Vercammen-Grandjean, 1956d: 79, pls 1C–D, 2C–D. Neotrombicula roubaudi – Zumpt 1961: 145. — Goff 1995: 12. Neotrombicula roubaudi roubaudi – Taufflieb 1960a: 46. Neotrombicula (Neotrombicula) roubaudi – Vercammen-Grandjean 1965c: 71. Holotype No data. Material revised Four paratypes from RMCA, not suitable for examination. Distribution Morocco (Oued Cherrat, Tit Mellil). Hosts Apodemus sylvaticus , Dipodillus campestris , Eliomys munbyanus , Lemniscomys barbarus , Mus spicilegus , M. spretus , Mustela nivalis numidica , Oryctolagus cuniculus , Paridae gen. sp., Passeriformes gen. sp., Rattus rattus. Published as part of Stekolnikov, Alexandr A., 2018, Taxonomy and distribution of African chiggers (Acariformes, Trombiculidae), pp. 1-233 in European Journal of Taxonomy 395 on page 182, DOI:10.5852/ejt.2018.395, http://zenodo.org/record/3829724